Evaluating the effect of roasting on coffee lipids using a hybrid targeted-untargeted NMR approach in combination with MRI. (30th November 2019) - Williamson, Kathryn; Hatzakis, Emmanuel
Highlights: NMR analysis was applied to determine the impact of roasting on coffee lipids. Targeted analysis was performed using an internal standard and PULCON. PULCON was in a very good agreement with the traditional method. Roasting affects coffee lipids, as found by targeted and untargeted analysis. MRI revealed important morphological alterations in bean structure. Abstract: An integrated targeted-untargeted 1 H and 13 C Nuclear Magnetic Resonance (NMR) analysis was applied to determine the impact of roasting on coffee lipids. For targeted analysis, both an internal standard (IS) method, as well as the ERETIC2 tool based on PULCON (Pulse Length-based Concentration determination), were used for quantitation. PULCON allows for quantitative analysis without sample contamination with an IS and was found to be in very good agreement with the traditional IS approach as indicated by a systematic Bland-Altman comparison study. For the untargeted analysis, NMR was coupled with multivariate statistical analysis (MVSA), namely Principal Component Analysis (PCA), Hierarchical Cluster Analysis (HCA), and Orthogonal Projection to Latent Structures Discriminant Analysis (OPLS-DA). 13 C NMR spectra were acquired using a z-stored spin-echo sequence to achieve higher spectral quality, which is important for both targeted and untargeted analysis. Results showed that roasting has a clear effect on coffee lipids, with diterpenes, oxidation/hydrolysis products and unsaturated fatty acid chains being the most significant markers. In addition, the application of MRI indicated important morphological alterations in bean structure and lipid migration from the endosperm to the surface of the coffee bean.